Inequality and democratization : an elite-competition approach - Ansell, Ben W., 1977-; Samuels, David, 1967- (New York, NY : Cambridge University Press, 2014)
"Research on the economic origins of democracy and dictatorship has shifted away from the impact of growth and turned toward the question of how different patterns of growth - equal or unequal - shape regime change. This book offers a new theory of the historical relationship between economic modernization and the emergence of democracy on a global scale, focusing on the effects of land and income inequality. Contrary to most mainstream arguments, Ben W. Ansell and David J. Samuels suggest that democracy is more likely to emerge when rising, yet politically disenfranchised, groups demand more influence because they have more to lose, rather than when threats of redistribution to elite interests are low"--
Machine generated contents note: 1. Introduction; 2. Inequality, development, and distribution; 3. Actors and interests; 4. An elite-competition model of democratization; 5. Assessing the relationship between inequality and democratization; 6. Inequality and democratization: empirical extensions; 7. Democracy, inequality, and public spending: reassessing the evidence; 8. Democracy, redistribution, and preferences; 9. Conclusion.
Includes bibliographical references (pages 211-226) and index.
Keywords: Democracy -- Economic aspects; Democratization -- Economic aspects; Economic development -- Political aspects; Land tenure -- Political aspects; Income distribution -- Political aspects; POLITICAL SCIENCE / General